(untitled) (Fiep Bulletin - online, 2012)
This study is an analysis of previous writings on sport philosophy, field of knowledge whichhas developed in the last decades of the 20th century. and its attempt to build an axiology of physicalactivity.Values in physical culture can be conferred to the activity as an ideal or to its practice for itself,having the first prevailed in our society’s mass culture and entertainment industry. Therefore, a newtheoretical paradigm with new values must be planed.